2020
DOI: 10.1021/acs.jpcb.9b10176
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Convex Nanopore Chemistry on Confined Water Dynamics

Abstract: A fundamental understanding of confined water is crucial for developing selective ion transport and water purification membranes, yet the roles of nanopore geometry and functionality on confined water dynamics remain unresolved. We report the synthesis of perdeuterated ionic alkylsulfonate amphiphiles and their water-induced self-assembly into lyotropic liquid crystal (LLC) mesophases with well-defined, convex, sulfonate-lined nanopores. Quasielastic neutron scattering (QENS) measurements demonstrate that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…We found that a KWW function provides a reasonable description of our data as the distribution of branch lengths along the polymer backbone of the PEI and variation in the local functional group environment should result in inhomogeneous contributions to dynamics, similar to many other systems where the KWW relationship has been employed. 33,34 The stretching exponent, β, in our fits was allowed to float between 0.5 and 1 in the fitting procedure but converged at the lower limit of 0.5 (typical for heterogeneous polymer systems 35 ) for the spectra obtained at 325 K (Figure S5). We show the trend in β vs Q without these limits in place for a few samples in Figure S5 where values continue to converge around 0.5.…”
Section: ■ Methodsmentioning
confidence: 99%
“…We found that a KWW function provides a reasonable description of our data as the distribution of branch lengths along the polymer backbone of the PEI and variation in the local functional group environment should result in inhomogeneous contributions to dynamics, similar to many other systems where the KWW relationship has been employed. 33,34 The stretching exponent, β, in our fits was allowed to float between 0.5 and 1 in the fitting procedure but converged at the lower limit of 0.5 (typical for heterogeneous polymer systems 35 ) for the spectra obtained at 325 K (Figure S5). We show the trend in β vs Q without these limits in place for a few samples in Figure S5 where values continue to converge around 0.5.…”
Section: ■ Methodsmentioning
confidence: 99%
“…The inter-diffusion of aqueous salts confined in mesoporous silica in contact with bulk water was also determined by following the depletion of salt concentration from monolithic samples using visible spectroscopy [306][307][308], or by measuring the increasing electrical conductivity of the water phase [296]. There are also 2123 some studies of self-diffusion of water confined in other 2124 materials, such as activated carbon [309], metal-organic 2125 nanotubes [310], and convex pores of alkylsulfonate 2126 amphiphiles [311], while the diffusion of ions confined 2127 in water nanofilms and nanodroplets was analyzed by 2128 synchrotron X-ray microprobe [312] and dielectric spec-2129 troscopy [313], respectively.…”
Section: Transport Properties Of Water and Ions Under Confinement: An...mentioning
confidence: 99%
“…These diverse properties of confined water open a new door to materials science and may play an important role in the future development of biology. For more details concerning the intriguing properties of confined water and its impact on materials properties, consider refs .…”
Section: Introductionmentioning
confidence: 99%